![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(72^{45}-72^{44}=72^{44}.\left(72-1\right)=72^{44}.71\)
\(72^{44}-72^{43}=72^{43}.\left(72-1\right)=72^{43}.71\)
Vì \(72^{44}>72^{43}\Rightarrow72^{45}-72^{44}>72^{44}-72^{43}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Câu 3:
\(2S=2+2^2+2^3+...+2^{10}\)
nên \(S=2^{10}-1\)
\(5\cdot2^8=256\cdot5=1280>1023=2^{10}-1\)
Do đó: \(S< 5\cdot2^8\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (x - 2)(x + 4) = 0
=> x - 2 = 0 hoặc x + 4 = 0
=> x = 2 hoặc x = -4
b) Đề lỗi
c) 72 - 3|x + 1| = 9
=> 3|x + 1| = 72 - 9
=> 3|x + 1| = 63
=> |x + 1| = 63 : 3
=> |x + 1| = 21
=> x + 1 = 21 hoặc x + 1 = -21
=> x = 20 hoặc x = -22
d) 7(x - 3) - 5(3 - x) = 11x - 5
=> 7x - 21 - 15 + 5x = 11x - 5
=> 7x - 21 - 15 + 5x - 11x + 5 = 0
=> x - 31 = 0
=> x = 31
![](https://rs.olm.vn/images/avt/0.png?1311)
1/ \(\left\{{}\begin{matrix}\left(x-2\right)^{72}\ge0\\\left(y+1\right)^{70}\ge0\end{matrix}\right.\)
Mà \(\left(x-2\right)^{72}+\left(y+1\right)^{70}=0\)
\(\Leftrightarrow\left\{{}\begin{matrix}\left(x-2\right)^{72}=0\\\left(y+1\right)^{70}=0\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}x-2=0\\y+1=0\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}x=2\\y=-1\end{matrix}\right.\)
Vậy ...
2/ \(\left\{{}\begin{matrix}\left|x+1\right|\ge0\\\left|y-3\right|\ge0\end{matrix}\right.\)
Mà \(\left|x+1\right|+\left|y-3\right|=0\)
\(\Leftrightarrow\left\{{}\begin{matrix}\left|x+1\right|=0\\\left|y-3\right|=0\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}x=-1\\y=3\end{matrix}\right.\)
Vậy ...
3/ \(\left\{{}\begin{matrix}\left(2x-10\right)^{100}\ge0\\\left(x-y\right)^{102}\ge0\end{matrix}\right.\)
Mà \(\left(2x-10\right)^{100}+\left(x-y\right)^{102}=0\)
\(\Leftrightarrow\left\{{}\begin{matrix}\left(2x-10\right)^{100}=0\\\left(x-y\right)^{102}=0\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}2x-10=0\\x-y=0\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}x=5\\y=5\end{matrix}\right.\)
Vậy ....
4/ \(\left\{{}\begin{matrix}\left|2x+8\right|\ge0\\\left|y+x\right|\ge0\end{matrix}\right.\)
Mà \(\left|2x+8\right|+\left|y+x\right|=0\)
\(\Leftrightarrow\left\{{}\begin{matrix}\left|2x+8\right|=0\\\left|y+x\right|=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}2x+8=0\\y+x=0\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}x=-8\\y=8\end{matrix}\right.\)
Vậy ..
![](https://rs.olm.vn/images/avt/0.png?1311)
31x72 - 31x70 - 31 x 2 - 31
=31x(72 -70 -2 -1)
=31 x (-1)
= -31
những câu sau thì lam tương tự nha bạn ^_^
=>(x-3)=o
=>x=3